1984
DOI: 10.1177/030098588402100608
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Pyrophosphate Deposition in Nonhuman Primates

Abstract: Abstract. Naturally occurring deposition of calcium pyrophosphate has been identified in six rhesus monkeys following acute episodes of trauma and various septicemias. Scanning electron microscopy with energy-dispersive X-ray analytical system and single crystal electron diffraction studies were used to identify the crystals within the articular cartilage. The osteoarthritis grading system was used to determine the degree of cartilage degenerative changes.Calcium pyrophosphate deposition disease (CPDD) is a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…CPPD, however, has been reported in a variety of nonhuman primates. 204 Both conditions are increased in older and elderly humans, with a mean age of 69 y for gout and 73 y for CPPD. 151 Men are more affected than women (82% of gout cases, 63% of CPPD).…”
Section: Types Of Nonseptic Arthritismentioning
confidence: 99%
“…CPPD, however, has been reported in a variety of nonhuman primates. 204 Both conditions are increased in older and elderly humans, with a mean age of 69 y for gout and 73 y for CPPD. 151 Men are more affected than women (82% of gout cases, 63% of CPPD).…”
Section: Types Of Nonseptic Arthritismentioning
confidence: 99%
“…In human beings, ageing, trauma, genetic factors, surgery and acute generalised illness appear to play a role in promoting calcium pyrophosphate deposition (Roberts and others 1984, Resnick and Niwayama 1995). It is suggested that these factors may result in increased metabolic turnover of articular cartilage, with subsequent crystal deposition (Roberts and others 1984). The cause for the deposition of the crystals in the joints of the two dogs presented here is not known but may have been associated with the infected carnassial tooth or tooth removal in case 2.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for crystal formation is unknown. In human beings, ageing, trauma, genetic factors, surgery and acute generalised illness appear to play a role in promoting calcium pyrophosphate deposition (Roberts andothers 1984, Resnick andNiwayama 1995). It is suggested that these factors may result in increased metabolic turnover of articular cartilage, with subsequent crystal deposition (Roberts and others 1984).…”
Section: Discussionmentioning
confidence: 99%
“…2), similar to the pattern noted in humans (Resnick and Niwayama, 1988;Rothschild, 1982;Rothschild and Woods, manuscript in preparation). Predominant lower extremity involvement with CPPD (Renlund et al, 1986;Roberts et al, 1984). Their observations may reflect the association of the CPPD with osteoarthritis (Moskowitz et al, 1984) or other aspects peculiar to an artificial (e.g., colony) environment.…”
Section: Discussionmentioning
confidence: 99%